Purwarupa Sistem Monitoring Kualitas Air pada Kolam Ikan Air Tawar - Arif Supriyanto; Fathurrahmani Fathurrahmani; agustian noor; yunita prastyaningsih (Ultimatics : Jurnal Teknik Informatika, 2019)
In freshwater fish cultivation, the most important thing to guard and pay attention to is the quality of pond water for the survival of these fish. The resilience of the body of the fish is very dependent on the quality of the water, if the water quality is good then the resistance of the body of the fish to the attack of the disease will be better too. This research was conducted to design and build a prototype monitoring system for freshwater fish pond water quality that can provide information about the condition of freshwater fish ponds in real-time. This monitoring system is made using Arduino as a data processor and several sensors such as water pH sensors, water turbidity, and water temperature. Next is a web-based monitoring application. This system can be monitored directly by fish farmers via LCD screens and smartphones. Based on the test results, the temperature sensor has an offset value of 0.34, pH sensor 0.37, turbidity sensor 0.22 and the fish management monitoring system application can function properly.